2021
DOI: 10.3390/atmos13010015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using a New Parameterization of Nucleation in the WRF-Chem Model on New Particle Formation in a Passive Volcanic Plume

Abstract: We investigated the role of the passive volcanic plume of Mount Etna (Italy) in the formation of new particles in the size range of 2.5–10 nm through the gas-to-particle nucleation of sulfuric acid (H2SO4) precursors, formed from the oxidation of SO2, and their evolution to particles with diameters larger than 100 nm. Two simulations were performed using the Weather Research and Forecasting Model coupled with chemistry (WRF-Chem) under the same configuration, except for the nucleation parameterization implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 129 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…For instance, in the study of NPF in East Asia in the spring of 2009, even after lowering the nucleation rate in a regional model of WRF-Chem applied in their study, the reduced number concentration of particles at 10-130 nm remained to be overestimated (Matsui et al, 2013). Using the same regional model and a similar method to reduce the nucleation rate, Arghavani et al (2022) found particle number concentration at 10-100 nm was still overestimated by nearly one order of magnitude, despite the effectiveness to reduce the overestimates for the smaller particles such as 2.5-10 nm. In addition to the rate of NPF, the growth process of particles also has a crucial effect on particle number concentration and size distribution.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, in the study of NPF in East Asia in the spring of 2009, even after lowering the nucleation rate in a regional model of WRF-Chem applied in their study, the reduced number concentration of particles at 10-130 nm remained to be overestimated (Matsui et al, 2013). Using the same regional model and a similar method to reduce the nucleation rate, Arghavani et al (2022) found particle number concentration at 10-100 nm was still overestimated by nearly one order of magnitude, despite the effectiveness to reduce the overestimates for the smaller particles such as 2.5-10 nm. In addition to the rate of NPF, the growth process of particles also has a crucial effect on particle number concentration and size distribution.…”
Section: Introductionmentioning
confidence: 98%
“…The overestimate of condensation nuclei (CN) in numerical models are commonly seen, despite the attempt to correctify the bias (Matsui et al, 2013;Arghavani et al, 2022). It is a common way to reduce the nucleation rate which may reduce the particle number concentration in proportion (Matsui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Etna and ordinary explosive activity at Stromboli. More recently, Arghavani et al 2022 [29] implemented a novel parameterisation of nucleation in the WRF-Chem model regarding new particle formation of a passive degassing of the Mt. Etna plume observed on 15 June 2016 [29].…”
Section: Introductionmentioning
confidence: 99%